Bank syariah : teori, praktik, dan peranannya - Perwataatmadja, Karnaen A. (Karnaen Anwar), 1940-; Tanjung, Hendri (Jakarta, Indonesia : Celestial Pub, 2007)
Islamic banks and monetary policies with reference to Indonesia
Includes bibliographical references (p. 289-296) and index
Keywords: Banks and banking -- Religious aspects -- Islam; Banks and banking -- Indonesia